History of Java Ethnic Migration in Kayu Aro District, Kerinci, Jambi - Friska Muflihun Soleh; Erniwati Erniwati (Pascasarjana, Universitas Negeri Padang, 2019)
Abstract Ethnic Javanese in Kayu Aro District are the majority ethnic in the middle of the Kerinci community settlement in Kayu Aro District. Even though there are migrants, the Javanese ethnic culture and customs in Kayu Aro Subdistrict are still carried out and maintained. Javanese ethnicity in Kayu Aro has a very important role in economic development in Kerinci Regency. The existence of ethnic Javanese since Dutch colonialism in Kayu Aro, has become an important history and needs to be known. This paper aims to reveal how the history of Javanese ethnic migration in Kayu Aro District. This study uses historical methods with heuristic data collection techniques, source criticism, interpretation, and historiography. The results showed that the migration of Javanese in Kayu Aro District originated from an ethical political program implemented by the Dutch colonial government, namely education, irrigation and migration. The Dutch colonial government brought ethnic Javanese to Kayu Aro sub-district as contract workers for tea plantations which began in 1928. However, along with the development of colonization, the Dutch colonial government experienced difficulties in providing workers salaries. Therefore, one way to pay for the salary, the Dutch colonial government gave each head of the family land to live outside of the HGU land.